Pop-Up Book Media Based on Pancasila Student Profiles to Support the Implementation of the Independent Curriculum - I Kadek Adi Purna Wibawa; Ni Wayan Rati (Universitas Pendidikan Ganesha, 2023)
Learning in schools does not use varied and interactive learning media because of the limitations of teachers in developing learning media. This study aims to develop a Pop-Up Book media based on Pancasila Student Profiles for grade I SD that has been tested for validity, practicality, and effectiveness. This research uses the ADDIE model, which consists of 5 stages: analysis, design, development, implementation, and evaluation. The subjects in this study were 16 grade 1 elementary school students. Research data were collected by questionnaire, observation, and test methods. The data were analyzed by qualitative and quantitative descriptive statistical analysis. The percentage of media expert test results is 92.31%, material expert test is 93.75%, learning design test results are 93.75%, individual trials are 90.83%, small group trials are 91.39%, and student response tests are 90.10%. The effectiveness test results showed a significant effect before and after using the Pop-Up Book media based on Pancasila student profiles on the learning outcomes of PPKn class I SD. The Pop-Up Book media developed is valid, practical, and effective as a supporting medium in the learning process.